Influence of a Nanometric Al2O3 Interlayer on the Thermal Conductance of an Al/(Si, Diamond) Interface1. Issue 1 (16th May 2014) - Monachon, Christian; Weber, Ludger
Abstract The effect of an Al2O3 interlayer on the thermal conductance of metal (Al)/non‐metal (diamond and silicon) interfaces is investigated using Time Domain ThermoReflectance (TDTR). Interlayers between 1.7 and 20 nm are deposited on oxygen‐terminated diamond and hydrogen‐terminated silicon substrates using atomic layer deposition (ALD). Their overall conductance is then measured at temperatures ranging from 78 to 290 K. The contributions of the interlayer bulk and its interfaces with both substrate and metallic overlayer are then separated. Values thus obtained for the bulk interlayer conductivity are comparable with existing data, reaching 1.25 W m−1 K−1 at 290 K. Interface contributions are shown to be very similar to the values obtained when a single Al/substrate interface is investigated, suggesting that interfacial oxides may govern TBC independently of the interlayer's thickness.